2016
DOI: 10.1093/cid/ciw865
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Antibody Responses 6 Years Following 1, 2, or 3 Doses of Quadrivalent Human Papillomavirus (HPV) Vaccine in Adolescent Fijian Girls, and Subsequent Responses to a Single Dose of Bivalent HPV Vaccine: A Prospective Cohort Study

Abstract: Two doses of 4vHPV provide similar NAb titers as 3 doses for 6 years, although the clinical significance is unknown. A single dose of 4vHPV elicits antibodies that persisted for at least 6 years, and induced immune memory, suggesting possible protection against HPV vaccine types after a single dose of 4vHPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 30 publications
7
45
0
Order By: Relevance
“…The secondary analyses were the comparison of the NAb GMTs one month post-2vHPV between girls who received zero, one or two doses and girls who received three doses. We also stratified the girls in each dosage group by ethnicity and compared their NAb GMTs based on our previous findings that vaccine-type NAb titres differed by ethnicity [22]. Within the two-dose group, we also stratified the girls into those who received two doses <6 months or ≥6 months apart, and compared their NAb GMTs before and one month after 2vHPV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The secondary analyses were the comparison of the NAb GMTs one month post-2vHPV between girls who received zero, one or two doses and girls who received three doses. We also stratified the girls in each dosage group by ethnicity and compared their NAb GMTs based on our previous findings that vaccine-type NAb titres differed by ethnicity [22]. Within the two-dose group, we also stratified the girls into those who received two doses <6 months or ≥6 months apart, and compared their NAb GMTs before and one month after 2vHPV.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study design, enrolled participants as well as study procedures have been described previously [22]. Briefly, a cohort study was conducted in Fiji between February and March 2015.…”
Section: Study Design Procedures and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the overall population, the rate of anal infection by HPV-16/18 was lower (62%) [47]. Additionally, a randomized, double-blind, placebo-controlled clinical trial with more than 4,000 healthy men aged 16–26 years showed a significant reduction in the risk of external genital lesions (including condylomas) in the group receiving the 4-valent vaccine, with 90% efficacy in the HPV-naïve group and 65% in the overall population [48]. …”
Section: Data From Clinical Trialsmentioning
confidence: 99%